2018
DOI: 10.3390/rs10020201
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing Seabed Topography from Side-Scan Sonar Images with Self-Constraint

Abstract: Abstract:To obtain the high-resolution seabed topography and overcome the limitations of existing topography reconstruction methods in requiring external bathymetric data and ignoring the effects of sediment variations and Side-Scan Sonar (SSS) image quality, this study proposes a method of reconstructing seabed topography from SSS images with a self-constraint condition. A reconstruction model is deduced by Lambert's law and the seabed scattering model. A bottom tracking method is put forward to get the along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 32 publications
(48 reference statements)
0
16
0
Order By: Relevance
“…In the past few years, extensive studies have shown that once a small amount of prior knowledge about the data is incorporated, the performance of clustering can be improved greatly [28], [43]. In order to use the background knowledge of data points reasonably, semi-supervised clustering is proposed.…”
Section: A Clustering and Semi-supervised Clustering Variantsmentioning
confidence: 99%
“…In the past few years, extensive studies have shown that once a small amount of prior knowledge about the data is incorporated, the performance of clustering can be improved greatly [28], [43]. In order to use the background knowledge of data points reasonably, semi-supervised clustering is proposed.…”
Section: A Clustering and Semi-supervised Clustering Variantsmentioning
confidence: 99%
“…Intensity of acoustic return converted to grey-level pixel value (0-255) as seabed image of side scan sonar. (Cervenka and de Mustier, 1993;Daniel, et al, 1998;Moreno et al, 2014, Burguera andOliver, 2015;Zhao et al, 2017. ).…”
Section: Introductionmentioning
confidence: 99%
“…Many previous works have proposed different methods to reconstruct bathymetry from sidescan [ 3 , 4 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. They can be categorized into different groups according to different criteria, see Table 1 .…”
Section: Introductionmentioning
confidence: 99%